2018
DOI: 10.18203/2320-6012.ijrms20182828
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of neoplastic and non-neoplastic lesions of ovary: a five-year study in a tertiary care centre of rural india

Abstract: Background: Most common ovarian lesions include benign non-neoplastic lesions including functional cysts and neoplastic lesions. While among cancers of female genital tract, the incidence of ovarian cancer ranks below only carcinoma of cervix and endometrium. The aim of this study was to observe and evaluate the frequency and morphological pattern of different ovarian pathologies encountered in this tertiary care centre of rural India.Methods: This was a retrospective five years observational study (2012-16) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
2
2
0
Order By: Relevance
“…In the present study out of total 160 non-neoplastic cases, follicular cyst was most common lesion 71 cases (44.38%) followed by 33 cases (20.625%) of corpus luteal cyst. Nearly similar results were reported by Maurya G. et al [9] and Gupta AK et al [10] . Out of 120 neoplastic lesions in our study there were 80 benign (66.67%), 8 borderline (6.66%) and 32 malignant lesions (26.67%), while M Thirukumar et al [11] .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In the present study out of total 160 non-neoplastic cases, follicular cyst was most common lesion 71 cases (44.38%) followed by 33 cases (20.625%) of corpus luteal cyst. Nearly similar results were reported by Maurya G. et al [9] and Gupta AK et al [10] . Out of 120 neoplastic lesions in our study there were 80 benign (66.67%), 8 borderline (6.66%) and 32 malignant lesions (26.67%), while M Thirukumar et al [11] .…”
Section: Discussionsupporting
confidence: 88%
“…Non-neoplastic lesions were more than neoplastic lesions. Similar larger proportion of nonneoplastic lesions 147 cases (55.68%) out of 264 ovarian lesions were reported by Maurya G. et al [9] . In the present study out of total 160 non-neoplastic cases, follicular cyst was most common lesion 71 cases (44.38%) followed by 33 cases (20.625%) of corpus luteal cyst.…”
Section: Discussionsupporting
confidence: 86%
“…This study showed most common age group for occurrence of ovarian tumor was in 20-29 years (36%), followed 30-39 years (23.6%), similar with the findings of other studies. 6,11,12,18,19 Ovarian tumor may occur at any age, including infancy and childhood. 18 The peak incidence is between 21 to 40 years and about 80% are benign.…”
Section: Discussionmentioning
confidence: 99%
“…In ovaries, the most common ovarian lesions include benign non neoplastic lesions and neoplastic lesions including functional cysts and ovarian tumors respectively. Ovarian lesions affect all age groups [5] . The clinical course of different histologic types of ovarian ~ 7 ~ tumors are much variable [6,7] .…”
Section: Introductionmentioning
confidence: 99%